2013
DOI: 10.1016/j.biomaterials.2013.03.038
|View full text |Cite
|
Sign up to set email alerts
|

The performance of silk scaffolds in a rat model of augmentation cystoplasty

Abstract: The diverse processing plasticity of silk-based biomaterials offers a versatile platform for understanding the impact of structural and mechanical matrix properties on bladder regenerative processes. Three distinct groups of 3-D matrices were fabricated from aqueous solutions of Bombyx mori silk fibroin either by a gel spinning technique (GS1 and GS2 groups) or a solvent-casting/salt-leaching method in combination with silk film casting (FF group). SEM analyses revealed that GS1 matrices consisted of smooth, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
79
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 28 publications
8
79
4
Order By: Relevance
“…Aqueous SF solutions were prepared from B. mori silkworm cocoons using published procedures [25] and utilized to construct a bi-layer SF matrix using methods previously described [24]. Briefly, an SF solution (8% wt/vol) was poured into a rectangular casting vessel and dried in a laminar flow hood at room temperature for 48 h to achieve formation of an SF film.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueous SF solutions were prepared from B. mori silkworm cocoons using published procedures [25] and utilized to construct a bi-layer SF matrix using methods previously described [24]. Briefly, an SF solution (8% wt/vol) was poured into a rectangular casting vessel and dried in a laminar flow hood at room temperature for 48 h to achieve formation of an SF film.…”
Section: Methodsmentioning
confidence: 99%
“…Bi-layer silk fibroin (SF) scaffolds derived from Bombyx mori silkworm cocoons as well as porcine small intestinal submucosa have been previously shown to promote defect consolidation and mediate functional voiding in non-diseased animal models of bladder augmentation [1824]. These matrices, therefore, represent potential candidates for neurogenic bladder repair; however their performance in the setting of neuropathogenic disease is currently unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Biomaterials used for scaffolding include both synthetic and naturally derived materials, and they are designed to provide structural support to maintain the overall shape of bladder and a favorable microenvironment for cell growth. Synthetic biomaterials such as polylactic-co-glycolic acid (PLGA) have been evaluated as scaffolds for bladder applications, and their suitability for supporting cells has been excellent in study results to date [42,43]. PLGA coated with collagen or fibrin has shown biocompatibility and supported cell growth and differentiation.…”
Section: Bladder Reconstructionmentioning
confidence: 98%
“…3 The polymeric suspension is poured onto molds and once the solvent gets evaporated, a homogenous membrane of composite material consisting of particles embedded in a polymer matrix will be formed, which can be gently peeled off from the surface of molds and stored in desiccator. 4 Composite membranes embedded with micro and nanoparticles are gaining lot of importance in the biomedical field. Liu et al, have reported increased proliferation and differentiation of pre-osteoblasts on nanostructured polypyrrole membrane.…”
Section: Introductionmentioning
confidence: 99%